Bahasa Indonesia Pengaruh Non Performing Loan (NPL), Biaya Operasional Dan Pendapatan Operasional (BOPO) Dan Loan to Deposit Ratio (LDR) Terhadap Return On Assets (ROA) Bank Persero - Anita Purwanti; Isro'iyatul Mubarokah (Peneliti.net, 2023)
Soundness level of a Commercial Bank can be assessed from several indicators. One of the main indicators used as the basis for the assessment is the related financial statements. Based on the financial statements, a number of financial ratios can be calculated to help businesspeople, both the government and other users of financial reports, in assessing the Bank's financial condition. This study aims to determine the effect of banking risk which is analyzed by influencing the ratio of NPL (Non Performing Loans), BOPO (Operating Costs and Operating Income), LDR (Loan to Deposit Ratio) to ROA (Return on Assets) of BUMN Banks. The data used in this study were obtained from the financial statements of state-owned banks registered with the Financial Services Authority. The number of bank samples studied were 4 state-owned banks registered with the Financial Services Authority for the 2019-2022 period. The data used in this study is secondary data in the form of quarterly financial reports. The research method used is multiple linear regression analysis processed using SPSS on the ratios of NPL, BOPO and LDR which significantly affect ROA. The results of this study indicate that the NPL and BOPO variables have a negative effect on ROA, and LDR has no effect on ROA.